IEEE Antennas and Propagation Society International Symposium. Digest. Held in Conjunction With: USNC/CNC/URSI North American R
DOI: 10.1109/aps.2003.1219383
|View full text |Cite
|
Sign up to set email alerts
|

Circular polarised printed antenna array with broadband axial ratio

Abstract: A new broadband prinfcd planar circular polarlied antema array is introduced. The'special features of the antenna array are: a) very large axial ratio (AR) bandwidth of 20% for AR better than 3 dB, h) high gain capability c) possibility to mnufacRlre antenna at IOW EOII (tolerance inrcnritivs) even at mi~mwave and m -w a v e range. Thc proposed concept is vcrificd at I S GHz and 60 GHz, showing a vcry good performance. Application of the proposed antenna concept may be for commerciaI low cos1 in-dwr m d out-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…However, linear polarized bandwidth is the main disadvantage of this antenna. Aimed to create circular polarization with broadband AR bandwidth of planar printed monopole antennas; many designs have been reported .…”
Section: Antenna Geometry and Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, linear polarized bandwidth is the main disadvantage of this antenna. Aimed to create circular polarization with broadband AR bandwidth of planar printed monopole antennas; many designs have been reported .…”
Section: Antenna Geometry and Simulationmentioning
confidence: 99%
“…Using the CP antenna this problem can be mitigated while allowing for reduction in interference from multipath reflections. Some papers have introduced 60 GHz CP antennas using PCB fabrication process .…”
Section: Introductionmentioning
confidence: 99%
“…A good review of various mmWave integrated circuit antennas can be found in [22]. Fur-thermore, several topologies of circularly polarized antenna have been proposed for the 60 GHz wireless communications [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve high performance for circularly polarized patch antennas, some new structures were reported in the literature, such as antennas array, stack layer antennas, using periodic structures [3][4][5][6][7], etc.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve high performance for circularly polarized patch antennas, some new structures were reported in the literature, such as antennas array, stack layer antennas, using periodic structures [3][4][5][6][7], etc.In this paper, a high performance circularly polarized low frequency patch antenna based on the compact fractal high-impedance surface EBG structure has been fabricated and experimented. The measured results show that the proposed circularly polarized patch antenna has good performance in impedance bandwidth, axial ratio (AR) bandwidth, and gain.…”
mentioning
confidence: 99%